2010
DOI: 10.1007/s12149-010-0382-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise capacity and cardiac diastolic function assessed by time–volume curve from 16-frame gated myocardial perfusion SPECT

Abstract: Our findings suggested that LV diastolic dysfunction, not systolic dysfunction, is associated with limited exercise capacity independent of the occurrence of ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…however, previous studies indicated that LV diastolic dysfunction rather than systolic function is associated with exercise intolerance (30,31), and PhHB/PhSD are related to diastolic function as described above. Although the mechanisms underlying the relationship between diastolic function and exercise capacity have not yet been elucidated in detail, previous studies provided some explanations (30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Relationship With Exercise Capacitymentioning
confidence: 80%
See 2 more Smart Citations
“…however, previous studies indicated that LV diastolic dysfunction rather than systolic function is associated with exercise intolerance (30,31), and PhHB/PhSD are related to diastolic function as described above. Although the mechanisms underlying the relationship between diastolic function and exercise capacity have not yet been elucidated in detail, previous studies provided some explanations (30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Relationship With Exercise Capacitymentioning
confidence: 80%
“…Moreover, LV diastolic dysfunction may be related to skeletal muscle weakness (36), particularly inspiratory muscle weakness (37), causing dyspnea and tachypnea during exercise. We discussed these matters in our previous study (31).…”
Section: Relationship With Exercise Capacitymentioning
confidence: 96%
See 1 more Smart Citation
“…Note that LAVI was identified as a primary echocardiographic metric relevant to the disablement process described by Verbrugge and Jette (1994).…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic dysfunction is a frequent cause of symptoms in heart failure (Zile, Baicu, & Gaasch, 2004) and is associated with increased mortality (Halley, Houghtaling, Khalil, Thomas, & Jaber, 2011). Moreover, diastolic function appears to correlate with exercise capacity better than systolic function in middle-aged and older patients with heart failure (Gardin et al, 2009; Yoshino, Nakae, Matsumoto, Mitsunami, & Horie, 2010). …”
mentioning
confidence: 99%